MENINGKATKAN KEMAMPUAN LITERASI EKOLOGI MELALUI PROGRAM EKOPILAH DI DESA SUKAMULYA - Irawan, Debi Krisna; Riandini, Resna; Yazid, Rivaldi Zakki; Sabarni, Rizka Mu'zizatin; Putri, Salsha Maura (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
Literacy is an individual's ability to understand and apply knowledge. Individual literacy in the context of environmental stewardship is rarely the main topic. Many assume that environmental literacy has become an awareness issue for every individual. However, various parties should consider environmental or ecological literacy essential and highly considered. All human beings should be aware of the importance of protecting the environment. Therefore, the effort to overcome these problems is to hold an Eko-pilah programme that utilises planning, socialisation, practice, and evaluation. The main target is elementary school children. Using this method, we can educate children about healthy lifestyles and how to sort waste based on the types of waste. This activity is carried out to raise awareness about the importance of ecological literacy from an early age to children. The goal is to empower the next generation to implement sustainable eco-sorting practices for their future lives. In addition, we also added a programme of making educational signs that were placed at several points to serve as reminder signs for the community members of Sukamulya village. The implementation of socialisation and the educational signs made the environment around Sukamulya village very clean and prevented more garbage from piling up. In addition, implementing socialisation and installing these signs can increase public awareness, especially among children, about the importance of protecting the environment where they live. Implementing this service provides valuable experiences for students and benefits the environment and the village community. This service activity increases understanding of ecological literacy in Sukamulya village.